Adjudin-loaded redox-sensitive paclitaxel-prodrug micelles for overcoming multidrug resistance with efficient targeted Colon cancer therapy. (1st January 2020) - Chen, Deli; Ge, Sitang; Zuo, Lugen; Wang, Shuanhu; Liu, Mulin; Li, Shiqing
Abstract: Multidrug resistance (MDR) is the primary cause for the failure of chemotherapy in the treatment of colon cancer. Recent research has indicated that the combination of a chemotherapeutic agent and a mitochondrial inhibitor might represent a promising strategy to help overcome MDR. However, for this approach to be clinically effective, it is important that the two drugs can be actively and simultaneously delivered into tumor cells at an optimal ratio and completely released drug within cells. To address these challenges, we designed and prepared a folate receptor-targeted and redox-responsive drug delivery system (FA- ss -P/A) that was able to co-deliver paclitaxel (PTX) and adjudin (ADD) to reverse colon cancer MDR. The PTX prodrug was obtained by conjugating PTX to dextrin via a disulfide-linkage. Then, folic acid (FA) was modified on the PTX prodrug. Finally, ADD, a mitochondrial inhibitor, was encapsulated in the PTX prodrug-formed micelles. A series of in vitro and in vivo experiments subsequently demonstrated that FA- ss -P/A can effectively reverse MDR by increasing cell uptake, inhibiting PTX efflux, and improving drug release.